Characterization of rock mass behaviour using mining induced microseismicity - C-I. Trifu; T. I. Urbancic (Canadian Institute of Mining, Metallurgy and Petroleum, 1997)
"ABSTRACTSeveral case studies are presented on the use of seismic techniques to map active structures, evaluate changes in stress levels, and identify the conditions leading to large magnitude seismic events and the generation of rock-bursts in Canadian mines. The results suggest that microseismicity can be used to identify the orientation of active fractures; define regions of relatively high and low stress, and those most likely to host a rockburst; determine the role of local stress on observed shear failures; and identify the path of stress transfer associated with the remote triggering of rockbursts. Additionally, the conditions leading to rock-bursts can be characterized by a significant increase in the clustering of microseismic events along the fault plane orientation of an impending event, and an increase in the effective stress levels. It is concluded that the analysis of microseismicity provides the means for remotely monitoring rock mass behaviour as a result of mining."